Experiment study on energy absorption of multi jet fusion printed cuttlebone-like structure - Lau, Zhan Yung (Nanyang Technological University, 2024)
In the aerospace and automotive industry, there is an increasing need for lightweight cellular structures for good energy absorbing capabilities. The cellular structures offer numerous benefits over conventional energy-absorbing materials and structures, making it a promising choice for applications such as impact protection, crashworthiness, and vibration damping. However, the metallic structures used are often expensive and heavier, thus polymeric structures become an alternative for the design considerations. Additive manufacturing technologies such as MultiJet Fusion (MJF) technology is particularly suitable for producing cellular structures due to its ability to cost effectively produce intricate and complex geometries with consistent mechanical properties. In this study, the objective is to investigate the effect of curvature walls on energy absorption of MJF printed cuttlebone-like structures. Four types of lattice structure, namely cuttlebone-like, half amplitude cuttlebone-like, symmetrical s-shape and straight wall structures were tested at different loading conditions to investigate their quasi static and dynamic compression energy absorption behavior. Furthermore, cuttlebone-like structure had the highest maximum energy absorption and peak load in both quasi static and dynamic compression tests. In quasi static tests, straight wall structure had the lowest energy absorption capability. In dynamic compression tests, symmetrical s-shape structures have the lowest energy absorption capability